1999
DOI: 10.1002/(sici)1096-8628(19990416)88:2<120::aid-ajmg4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the 5-HT6 receptor gene in schizophrenia

Abstract: Serotonergic (5-hydroxytryptamine; 5-HT) transmission may play an important role in the treatment and/or pathogenesis of schizophrenia. Previous studies reported that several atypical antipsychotic agents have high affinities for the 5-HT6 receptor. The 5-HT6 receptor gene polymorphism might contribute to the genetic background of this disorder. One hundred and fifty unrelated patients with schizophrenia and 150 unrelated healthy controls were genotyped for a biallelic polymorphism (267C/T) at the 5-HT6 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…In this study, no association was found between the (GCC) 2/3 polymorphism and suicide victims. In the 267C/T and (GCC) 2/3 polymorphisms, the genotype and allele distributions in this study were almost consistent with those previously reported by Shinkai et al 28 . and Ohmori et al ., 24 respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, no association was found between the (GCC) 2/3 polymorphism and suicide victims. In the 267C/T and (GCC) 2/3 polymorphisms, the genotype and allele distributions in this study were almost consistent with those previously reported by Shinkai et al 28 . and Ohmori et al ., 24 respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Positive associations were found between the 267T allele and schizophrenia, 29 and between the 267C allele and bipolar affective disorder, 25 but other studies 28,30 did not find an association between the 5‐HT 6 receptor gene and either schizophrenia or affective disorder. Thus, the results are still greatly inconclusive about the association of 5‐HT 6 receptor gene with specific psychiatric disorders.…”
Section: Discussionmentioning
confidence: 93%
“…Clozapine exhibits significant 5-HT 6 receptor antagonism, while quetiapine does not interact significantly with this receptor. Some studies have found altered 5-HT 6 mRNA expression in schizophrenia patients (East et al, 2002), and a 5-HT 6 polymorphism has been reported to be a risk factor for schizophrenia (Tsai et al, 1999; but see Shinkai et al, 1999; Ohmori et al, 2001) and to affect the therapeutic response to clozapine treatment (Yu et al, 1999; Huezo-Diaz et al, 2001). Selective 5-HT 6 receptor antagonists have been found to improve performance in a range of cognitive tasks in adult (Rogers and Hagan, 2001; Woolley et al, 2001; Hatcher et al, 2002; Hirst et al, 2003; King et al, 2004; but see Lindner et al, 2003) and aged rats (Foley et al, 2004; Kwon et al, 2004; Hirst et al, 2006), and attenuate memory impairment induced by anticholinergic drugs (Meneses, 2001; Szczepanski et al, 2002; Hirst et al, 2003, 2006; Woolley et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al (1999) reported that HTR6 was associated with schizophrenia in the Chinese population. However, the remaining studies showed no association (Shinkai et al, 1999;Vogt et al, 2000;Chiu et al, 2001). To overcome the limitation of heterogeneous results in the dominant model, a replication study using larger samples or samples of other populations will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al (1999) reported that HTR6 was associated with schizophrenia in the Chinese population. However, other studies, including two studies using Japanese samples, showed no association (Shinkai et al, 1999;Vogt et al, 2000;Chiu et al, 2001;Ohmori et al, 2002). Prior association studies using the "candidate gene approach" had the serious problem of having included relatively small samples, including only between 46-186 schizophrenia patients and 46-163 controls.…”
Section: Introductionmentioning
confidence: 99%